Early versus late salvage abdominoperineal resection for anal squamous cell carcinoma: Is there a difference in survival?. Issue 2 (4th May 2019) - Fields, Adam C.; Melnitchouk, Nelya; Senturk, James; Irani, Jennifer; Bleday, Ronald; Goldberg, Joel
Abstract: Background/Objectives: The first‐line treatment for anal squamous cell carcinoma is Nigro protocol chemoradiotherapy. Some patients will fail curative intent chemoradiotherapy and have persistent disease while others may have an initial response followed by disease recurrence. The goal of this study is to investigate survival in anal squamous cell carcinoma patients who fail first‐line treatment. Methods: The National Cancer Database (2004‐2013) was used to identify patients with anal squamous cell carcinoma. The primary outcome was overall survival. Results: There were 256 patients in the early salvage group who underwent abdominoperineal resection (APR) within 6 months of completing chemoradiotherapy and 181 patients in the late salvage group who had APR 6 months or more after completion of chemoradiotherapy. Both groups of patients had similar tumor size (45 vs 50 mm; P = 0.07) and rate of positive margins (21.5% vs 15.6%; P = 0.13). There was no significant difference in overall survival between early and late salvage APR (hazard ratio [HR]: 0.81; 95% confidence interval [CI]: 0.50‐1.32; P = 0.40). Conclusions: The overall survival of anal squamous cell carcinoma patients undergoing early vs late salvage APR after failure of chemoradiotherapy is similar. As a result, patients with persistent disease should be offered surgery just as readily as those with recurrent disease.